KEBERADAAN BADAN ARBITRASE NASIONAL INDONESIA SEBAGAI PILIHAN PENYELESAIAN SENGKETA HUTANG PIUTANG - ACHMAD RIVANDY NASUTION (PREMISE LAW JURNAL, 2015)
The national institutional arbitration in Indonesia is BANI (Indonesian National Arbitration Board. The research used judicial normative and descriptive analytic method. The data were gathered by using secondary data which consisted of primary, secondary, and tertiary legal materials as the main data. The obstacles in implementing arbitration decision in settling the dispute in debt and credit in Indonesia consists of judicial obstacles which comprise the execution which cannot automatically be implemented, there is still another decision which can be made after arbitration decision, and the settlement by the arbitration board is very limited. Technical obstacles consist of the lack of arbiters, the lack of information about the existence of BANI, and the highly dominant skill of arbiters. The attempts made by BANI to cope with the obstacles are by setting up a standard for arbitration clause such as the types of problem which can be settled through arbitration, the appointment of arbitration, the prevailing legal provisions, laws, and regulation, and the publication of quarterly bulletins, either in Indonesian or in foreign languages, so that people will know and understand the existence of arbitration board with all its functions as an alternative in settling disputes in business outside of Court. Keywords: Arbitration, BANI, Settling Dispute